The Synchronization of Classical Islamic Jurisprudence and National Regulations in the Distribution of Zakat fitrah to Islamic Boarding Schools in Indonesia - Syairi, Ahmad; Amalia, Dini Rezki; Norliana, Novi (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
The distribution of zakat fitrah (obligatory alms at the end of Ramadan) to pesantren (Islamic boarding schools) remains a subject of debate both in classical fiqh (Islamic jurisprudence) discourse and within the context of national zakat regulations in Indonesia. The lack of clarity regarding theological and juridical legitimacy creates ambiguity in the practice of distributing zakat fitrah to Islamic educational institutions. This research aims to analyze how zakat fitrah is positioned from a classical fiqh perspective, how zakat regulations in Indonesia govern its distribution to pesantren, identify gaps between the two, and formulate a synchronization model that can serve as a foundation for the legitimate and effective distribution of zakat fitrah to pesantren. The research employs a qualitative approach using the library research method. Primary data were obtained from fiqh texts of the four madhhabs (schools of Islamic jurisprudence), fatwas (religious legal opinions) of the Indonesian Council of Ulama (Majelis Ulama Indonesia), and formal regulations such as Law Number 23 of 2011 concerning Zakat Management. Secondary data include journal articles and related academic literature. Data analysis employs content analysis methods, incorporating thematic and comparative approaches, based on maqashid al-shari'ah (the objectives of Islamic law). Classical fiqh limits fi sabilillah (in the path of Allah) to physical jihad (struggle), but contemporary interpretation expands it to include Islamic education. Indonesian regulations do not provide explicit provisions regarding zakat fitrah distribution to pesantren, resulting in a diversity of practices in the field. Gaps are identified in aspects of recipients, interpretation of fi sabilillah, distribution mechanisms, and accountability. Case studies reveal distribution practices based on 'urf (custom) and local scholarly authority, particularly in Aceh and Java. A synchronization model based on shar'i (legal-religious) legitimacy, legal certainty, and accountability is needed through: regulatory affirmation of contemporary fi sabilillah, objective criteria for recipient pesantren, verification systems, and public education. This synchronization is essential to optimize the role of zakat as an instrument of welfare and empowerment of Islamic education in Indonesia.